Influence of Mesalazine on Ferroptosis-Related Gene Expression in In Vitro Colorectal Cancer Culture - Joanna Słoka; Barbara Strzałka-Mrozik; Sebastian Kubica; Ilona Nowak; Celina Kruszniewska-Rajs (Biomedicines)
Background/Objectives: Colorectal cancer (CRC) is one of the most common oncological disorders. Its fundamental treatments include surgery and chemotherapy, predominantly utilizing 5-fluorouracil (5-FU). Despite medical advances, CRC continues to present a high risk of recurrence, metastasis and low survival rates. Consequently, significant emphasis has been directed towards exploring novel types of cell death, particularly ferroptosis. Ferroptosis is characterized by iron imbalance and the accumulation of lipid peroxides and reactive oxygen species (ROS), leading to cellular damage and death. Thus, the discovery of safe inducers of ferroptosis, offering new hope in the struggle against CRC, remains crucial. In this study, we applied the concept of drug repositioning, selecting mesalazine (MES), a non-steroidal anti-inflammatory drug (NSAID), for investigation. Methods: The study was conducted on the colon cancer cell line DLD-1 and normal intestinal epithelial cells from the CCD 841 CoN cell line. Both cell lines were treated with MES solutions at concentrations of 10, 20, 30, 40, and 50 mM. Cytotoxicity was assessed using the MTT assay, while ferroptosis-related gene expression analysis was performed using oligonucleotide microarrays, with RT-qPCR used for validation. Results: MES effectively reduces the viability of DLD-1 cells while minimally affecting normal intestinal cells. Subsequent oligonucleotide microarray analysis revealed that MES significantly alters the expression of 56 genes associated with ferroptosis. Conclusions: Our results suggest that MES may induce ferroptosis in CRC, providing a foundation for further research in this area.